The process of building plan approval - Adanan, Nurul Syafina (Universiti Teknologi MARA, Perak, 2019)
This report aimed is to explain the building plan process for approval by local authority in Municipal Council Port Dickson (MCPD), Negeri Sembilan. This was the main objective of this report. Apart of that, several problems occurred during the process were also identified and solutions to solve the problems also have been discussed. To achieve objectives above, there were two research methods were undertaken such as interviews and document reviews. Nevertheless, there was no observation has been conducted in this study. The findings revealed that building plan process approval had two categories such as individual house or bungalow and project.